Effectiveness of Abdominal Activation on Motor Control in Diplegic Cerebral Palsy: A Randomized Control Trial - Lieza Iftikhar, Asma Sattar, Sana Qaisar, Faiza Altaf, Kanwal Fatima, Rabia Shahzadi, Mafia Shafique, Muhammad Aqeel, Hira Rafique, Intsam Aslam (Pakistan Journal of Medical & Health Sciences, 2024)
Background: Cerebral palsy (CP) is a disorder of the nervous system manifested in movement, posture, muscle tone, and functional activity. Poor postural control is the most common problem related to CP. Neuro-developmental techniques, or facilitation techniques, were used to activate muscles and improve trunk control. Aim: To determine the influence of the effects of abdominal activation for correcting posture in spastic diaplegic CP children. Methods: A quantitative, randomized clinical trial was conducted, allocating 26 CP patients randomly into two groups: the control group and the treatment group. Baseline treatment was given to the control group, which included lower-limb passive stretching exercises and interrupted direct current. However, baseline treatment with neuro-developmental techniques was given to the treatment group. The measuring tool used for assessment of postural correction and stability was the trunk control measurement scale. Results: The study recruited 26 CP patients, of who 10 belonged to the age groups 8–10 years and 11–13 years, respectively, while 6 children were from the age group 14–15 years. An independent sample t-test was used for between-group analysis, and the results showed a significant improvement in the TCMS score post-treatment, as the p-value was 0.012, while within-group analysis was done by applying a paired sample t-test. There was a significant improvement in the treatment group (p-value 0.000) where NTD was applied, compared to the control group (p-value 0.096), where only baseline treatment was given. Implication: Neurodevelopmental approaches can improve trunk control in children with cerebral palsy, enhancing mobility, independence, posture, and functional skills. This reduces the risk of musculoskeletal issues and facilitates activity participation. Conclusion: The study showed significant improvement in postural control with the use of Neuro-developmental techniques in CP children. Children with cerebral palsy (CP) can benefit from improved trunk control using neurodevelopmental approaches, which can increase their mobility, independence, posture, ability to participate in activities, and functional skills. Keywords: Cerebral palsy (CP), Neuro-developmental techniques (NDT), Interrupted direct current (IDC).